Anti-tumor properties of microwave-assisted synthesized 6,7-dihydroxycoumarins: An in vitro study - Tekin, Suat; Koran, Kenan; Ozen, Furkan; Gorgulu, Ahmet Orhan; Sandal, Suleyman (Wiley-Blackwell, 2015)
[Abstract Not Available]